NEWBORN CARE PRACTICES AMONG SLUM DWELLERS IN ALIGARH CITY, UTTAR PRADESH - Khan, Mohd. Haroon; Khalique, Najam; Siddiqui, Abdul Razzaq; Amir, Ali (Indian Journal of Community Health, 2013)
Background: The newborn health challenge faced by India is more formidable than that experienced by any other country in the world. The current neonatal mortality rate (NMR) of 44 per 1,000 live births, accounts for nearly two-thirds of all infant mortality and translates into at least two newborn deaths every minute. Methods: The present community based study was conducted in the field practice area of the Urban Health Training Centre (UHTC), Department of Community Medicine, Jawaharlal Nehru Medical College, Aligarh Muslim University, Aligarh, Uttar Pradesh, India. Purposive sampling i.e. nonrandom sampling to include subjects that serve the specific purpose was used. Two hundred pregnant women were chosen for the study. The study was carried out from one year. Data were analyzed with Epi Info version 3.5.1. Percentages, and Chi Square Test used. Objective was to study the knowledge and practices related to newborn care among slum dwellers in Aligarh, UP. Results: Majority of pregnant women (75%) had more than one live issue. Majority of pregnant women 91.5% delivered at home by untrained dais. Unhygienic delivery practices were common. There were low level of breastfeeding practices, practices to prevent hypothermia and knowledge of danger signs in newborns requiring medical consultation, among pregnant women in periurban area of Aligarh, Uttar Pradesh India. Conclusion: It was concluded that there was a poor newborn care practices among slum dwellers in Aligarh.